Hand Function A Practical Guide to Assessment - Duruöz, Mehmet Tuncay (Springer New York : Imprint: Springer, 2014)
Accurate assessment of hand function is critical to any treatment regimen of the hand compromised patient. Hand Function is a practical, clinical book which provides the knowledge needed to distinguish the different dimensions of hand function, particularly impairment, disability and handicap. Beginning with an overview of basic principles and examination, subsequent chapters evaluate the hand function in specific afflicted populations, including the rheumatoid patient, the stroke patient, the trauma patient, the geriatric patient and the pediatric patient, as well as special populations such as diabetes mellitus patients and musicians. An appendix containing hand function scales essential to the assessment of disability is also included. Rheumatologists, physiatrists, hand surgeons, orthopedists, occupational therapists and physical therapists will all find Hand Function a useful and valuable addition to their clinical references.